Sociodemografía y epidemiología de la población atendida en un centro de atención psicológica en México - Galindo Soto, Jonathan Alejandro; Maya-Perez, Eloy; Junco-Méndez, Francisca del Carmen; Jiménez-González, María de Jesús; Moya-González , Ivonne (Horizonte Sanitario, 2022)
Objective: It was to analyze the sociodemographic and diagnostic characteristics of the population attending psychotherapy. Materials and Method: Design was quantitative, descriptive, retrospective and longitudinal of 322 files. Results: It was found that the majority is male (60%), young (33%), Catholic (81%) and with basic school (26%). Females present more anxiety disorders (56%), related to trauma and stressors (71.4%), personality (75%), primary support group (65%), child neglect (80%), abuse (71.4%) and others related to social environment (62.5%). Males had neurodevelopmental (100%), impulse control/ behavioral (70%) and family upbringing (54.4%) problems. Most frequent problems are the parent-child relationship (14.6%), conflicts with the partner (8.9%) and life phase (6.1%). Conclusions: Instead of individual problems, most of population (especially women) attended derive from difficulties in their environment (insecurity, poverty) or from the lack of social skills to manage their interpersonal relationships in an assertive manner (parenting styles, resolution of couple problems). Aggressive masculinity is present in many situations, even when patients did not realize it when attending the service. Keywords: Mental health services; mental disorders; psychotherapy; population characteristics; gender and health